2021
DOI: 10.1093/eurheartj/ehab081
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein(a) is associated with large artery atherosclerosis stroke aetiology and stroke recurrence among patients below the age of 60 years: results from the BIOSIGNAL study

Abstract: Aims Lipoprotein(a) [Lp(a)] is a recognized causal risk factor for atherosclerotic cardiovascular disease but its role for acute ischaemic stroke (AIS) is controversial. In this study, we evaluated the association of Lp(a) with large artery atherosclerosis (LAA) stroke and risk of recurrent cerebrovascular events in AIS patients. Methods and results For this analysis of the prospective, observational, multicentre BIOSIGNAL co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(52 citation statements)
references
References 48 publications
1
48
0
3
Order By: Relevance
“…The associations between the Lp(a) level and an increased risk of atherosclerosis in different vascular beds, large artery atherosclerotic stroke, and calcification of the aortic valve have been well-demonstrated in large-scale studies [166][167][168][169][170][171][172]. These associations apply to different ethnicities and may be independent of LDL-C.…”
Section: Lipoprotein(a)mentioning
confidence: 89%
“…The associations between the Lp(a) level and an increased risk of atherosclerosis in different vascular beds, large artery atherosclerotic stroke, and calcification of the aortic valve have been well-demonstrated in large-scale studies [166][167][168][169][170][171][172]. These associations apply to different ethnicities and may be independent of LDL-C.…”
Section: Lipoprotein(a)mentioning
confidence: 89%
“…Perioperative stroke is a severe complication after cardiac surgery, and has the greatest influence of all potential adverse events [ 14 , 22 ]. It has been shown that elevated Lp(a) on admission is an independent risk factor for subsequent adverse cardiovascular events in patients with coronary artery disease [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the BIOSIGNAL study, Arnold et al reported on the association between elevated Lp(a) levels and large-artery atherosclerosis stroke. The group concluded that elevated Lp(a) levels were independently associated with stroke aetiology and risk of recurrent cerebrovascular events among primarily Caucasian individuals with evident arteriosclerotic disease [ 14 ]. We found no association between different Lp(a) levels and perioperative stroke; however, the incidence of stroke after the perioperative period was not assessed in the current study period.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Las partículas remanentes cargadas de apolipoproteína B aumentan el riesgo de mortalidad y de infarto agudo de miocardio cuando el colesterol unido a lipoproteínas de baja densidad está bajo 16 , y cada vez es mayor la implicación de lipoproteína a en el riesgo de ictus 17 y eventos cardiovasculares.…”
Section: Lípidosunclassified